Long-Term Prognostic Implications of the Admission Shock Index in Patients With Acute Myocardial Infarction Who Received Percutaneous Coronary Intervention. (April 2017) - Abe, Naoyuki; Miura, Takashi; Miyashita, Yusuke; Hashizume, Naoto; Ebisawa, Soichiro; Motoki, Hirohiko; Tsujimura, Takuya; Ishihara, Takayuki; Uematsu, Masaaki; Katagiri, Toshio; Ishihara, Ryuma; Tosaka, Atsushi; et al.
The admission shock index (SI) enables prediction of short-term prognosis. This study investigated the prognostic implications of admission SI for predicting long-term prognoses for acute myocardial infarction (AMI). The participants were 680 patients with AMI who received percutaneous coronary intervention. Shock index is the ratio of heart rate and systolic blood pressure. Patients were classified as admission SI <0.66 (normal) and ≥0.66 (elevated; 75th percentile). The end point was 5-year major adverse cardiac events (MACEs). Elevated admission SI was seen in 176 patients. Peak creatine kinase levels were significantly higher and left ventricular ejection fraction was lower in the elevated SI group, which had a worse MACEs. In multivariate Cox regression analysis, SI ≥0.66 was a risk factor for MACE. Elevated admission SI was associated with poorer long-term prognosis.